‘Spaces’ for restorative development: international case studies on restorative services - Hobson, Jonathan (Contemporary justice review, 2022)
This paper examines the concept of the ‘spaces’ into which restorative services develop. We conceptualise such ‘spaces’ as: social, the people and communities; as political, the will for developments; as physical, the geography and facilities; and as economic, dependent on the resources available. The first case study examines the hub-and-spoke model from Gloucestershire, England, where a top-down approach with buy-in at the statutory level provides ‘space’ for institutional engagement and integration of restorative practice. The second examines community-led restorative services in Belfast, Northern Ireland, originally tackling paramilitary violence they now fill a ‘space’ in local communities caused by a distrust of the state. The final case study is from Kenema City, Sierra Leone, where a post-conflict and post-Ebola ‘space’ is filled by an urban agriculture scheme aiming to divert young people from harmful activity and to reintegrate into society. Across the three cases in this paper, we hope to show that the types of ‘space’ we identify can be an important conceptual tool in helping to understand how and why restorative services develop, the provision they offer, and the capacities they haves to expand.